Pyuria predicts poor prognosis in patients with non-muscle-invasive bladder cancer treated with bacillus Calmette-Guérin - AZUMA, TAKESHI (Mol Clin Oncol, 2015)
This study was conducted to evaluate the utility of pyuria as a predictive marker of bacillus Calmette-Guérin (BCG) treatment for non-muscle-invasive bladder cancer (NMIBC). A cohort of 243 NMIBC patients treated with BCG through intravesical instillation between 1994 and 2007 at the Tokyo Metropolitan Tama Medical Center were enrolled in this retrospective study. Pyuria was defined as urine containing ≥10 white blood cells per high-power field. A total of 30 of the patients with pyuria (30/37, 81%) and 87 patients of those without pyuria (87/206, 42%) exhibited recurrence following BCG treatment. The 3-year recurrence-free survival rate of patients with and without pyuria following BCG treatment was 20 and 62%, respectively. The multivariate Cox proportional hazards regression model indicated that pyuria was an independent predictor of disease recurrence following BCG treatment. Patients with inflammatory NMIBC exhibited resistance to therapy with intravesical instillation of BCG.